The Influence of Child Care on Maternal Health and Mother-Child Interaction - Alexandra Kröll; Rainald Borck (Center for Economic Studies and ifo Institute (CESifo), 2013)
In Germany, formal child care coverage rates have increased markedly over the past few decades. The present paper is concerned with how mothers' mental and physical health is affected by whether they place their child in formal day care or not. Furthermore, the effects of formal child care usage on mother-child interaction are examined. The analysis is based on data provided by the German Socio-Economic Panel for the years 2006 to 2010. This data is analysed by means of regression analyses, using local aggregate formal child care usage rates as an instrument for individual formal child care usage. The results indicate that mothers are in a worse physical condition if their children attend formal care, whereas no such effect is found with regard to mothers' mental health. Overall, there is evidence that mothers placing their children in formal day care interact with them more frequently.
Keywords: J13; I12; 330; child care; health status; mother-child interaction